2022
DOI: 10.2486/indhealth.2021-0174
|View full text |Cite
|
Sign up to set email alerts
|

Does breaking up sitting in office-based settings result in cognitive performance improvements which last throughout the day? A review of the evidence

Abstract: Sedentary behavior at work contributes to detrimental cognitive outcomes (e.g., decreases in attention). The length of time that cognitive performance benefits are sustained following bouts of breaking up sitting (e.g., using sit-stand desks or walking) is not known. A narrative review of the literature was conducted using a systematic search strategy, with keywords related to breaking up sitting interventions in office-based environments and cognitive performance outcomes in the period immediately post the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In comparison, ResNet-18 was more highly activated by movements rather than postural changes. The movement patterns identified by ResNet-18 may reflect the differences in psychomotor function (e.g., reaction time) reported after breaking up sitting in previous research [11,[56][57][58]. Previous studies have reported improvements in psychomotor function, reaction time, and attention for cognitive tasks after breaking up sitting with light-to-moderate intensity physical [13,57,59].…”
Section: Discussionmentioning
confidence: 85%
“…In comparison, ResNet-18 was more highly activated by movements rather than postural changes. The movement patterns identified by ResNet-18 may reflect the differences in psychomotor function (e.g., reaction time) reported after breaking up sitting in previous research [11,[56][57][58]. Previous studies have reported improvements in psychomotor function, reaction time, and attention for cognitive tasks after breaking up sitting with light-to-moderate intensity physical [13,57,59].…”
Section: Discussionmentioning
confidence: 85%
“…Consistent light-intensity physical activity throughout the night shift could promote sufficient psycho-physiological arousal to result in cognitive, alertness, and mood improvements while on shift 86 , 87 . A narrative review of eight studies exploring the impact of breaking up sitting with light-intensity physical activity (e.g., 3 min of walking every 30 minutes) in sedentary day workers ( N = 256) found that breaking up sitting resulted in cognitive improvements in domains such as reaction time and attention 87 . It is unknown whether the effect of multiple bouts of physical activity on cognition, as a marker of adaptation, could extend to night workers experiencing circadian misalignment.…”
Section: Within Shiftmentioning
confidence: 99%
“…In sedentary shift workers who are at increased risk of ‘lifestyle illnesses’, breaking up sitting throughout day and night shift may be a method to reduce the likelihood of disease pathogenesis, and increase long-term coping with the shift work lifestyle. However, much of the breaking up sitting literature examines intervention outcomes in day working samples 75 , 87 , 117 119 . Thus, the impact of circadian misalignment on cardiometabolic health outcomes in response to a breaking up sitting intervention in shift working populations is currently unknown, though research on this is underway 120 .…”
Section: Within Work-spanmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 Although periodic movement breaks have been hypothesised to improve central and peripheral vascular function through altered shear stress, vasodilating mediators such as nitric oxide, prostaglandins and vascular compliance, evidence regarding the intensity of these breaks remains under debate. 8 , 12 Moderate to vigorous physical activity is well established to improve adult endothelial function. 13 , 14 Early laboratory studies have suggested a similar favourable vascular benefit with light-intensity activities; however, recent meta-analytic studies have revealed limited evidence regarding the favourable vascular effects of movement breaks or ‘snackivity’.…”
Section: Introductionmentioning
confidence: 99%
“… 16 The effectiveness of physical activity breaks remain uncertain, because most studies have manipulated the frequency and duration of physical activity breaks but not the intensity—a factor potentially linking physical activity breaks to favourable vascular function in adults. 12 …”
Section: Introductionmentioning
confidence: 99%